The relationship between serum lipid levels and colorectal serrated lesions: A systematic review and meta-analysis - Wang, Xuerui; Zou, Yangbin; Zhang, Ruxuan; Teng, Chunyan; Ren, Xuejiao; Zhang, Haishan; Zhou, Liting (Frontiers in Physiology, 2022)
Objective: To clarify the relationship between colorectal serrated lesions and serum lipid levels, and to provide a scientific basis for the identification and early clinical prevention and treatment of potential high-risk population of serrated colorectal lesions. Methods: Studies comparing the patients with colorectal serrated lesions and the controls in serum lipid levels were searched from PubMed, Embase, Web of Science, the Cochrane Library, China Biomedical Literature Database, CNKI, Wanfang Database and VIP Database. Relevant literatures were screened according to inclusion and exclusion criteria. The mean and standard deviation of serum lipid levels in patients and controls were extracted from the included literature. Combined weighted mean difference (WMDs) and 95% confidence interval (CIs) were calculated using STATA.V.16.0 software to evaluate the relationship between serum lipid levels and colorectal serrated lesions. The publication bias of the included studies was evaluated by Egger test. Results: Twenty-three literatures were included, including 2063 patients and 63909 controls. The level of serum high-density lipoprotein cholesterol (HDL-C) in case group was significantly lower than that in control group (WMD= -0.122mmol/L, 95%CI: -0.170-0.073). While the level of total cholesterol (TC), the level of low-density lipoprotein cholesterol (LDL-C) and the level of serum triglyceride in the case group were significantly higher than those in control group, and the WMD were 0.180mmol/L (95%CI: 0.061-0.299), 0.155mmol/L (95%CI: 0.038-0.273) and 0.241mmol/L (95%CI: 0.181-0.302) respectively. Conclusion: Colorectal serrated lesions may be related to blood lipid levels. Hyperlipidemia might be a risk factor for colorectal serrated lesions.